2014
DOI: 10.3920/bm2013.0039
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Bifidobacterium breve NCC2950 against DSS-induced colitis is dependent on bacterial preparation and timing of administration

Abstract: Probiotics have been proposed as a therapy for inflammatory bowel disease, but variations in strains, formulations, and protocols used in clinical trials have hindered the creation of guidelines for their use. Thus, preclinical insight into the mechanisms of specific probiotic strains and mode of administration would be useful to guide future clinical trial design. In this study, live, heat inactivated (HI), and spent culture medium preparations of the probiotic Bifidobacterium breve NCC2950 were administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…Serum IL‐10 concentration and IL‐10 mRNA expression of the intestinal mucosal lesions in active UC patients was significantly increased compared to normal control (Kucharzik, Stoll, Lügering, & Domschke, ; Mullin, Vezza, & Sampat, ). This was in line with some reports on animal with chronic colitis (Hayes et al., ; Moon et al., ). Therefore, low expression of IL‐10 mRNA in F935 group indicated reduction of inflammation in F935 mice of colitis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Serum IL‐10 concentration and IL‐10 mRNA expression of the intestinal mucosal lesions in active UC patients was significantly increased compared to normal control (Kucharzik, Stoll, Lügering, & Domschke, ; Mullin, Vezza, & Sampat, ). This was in line with some reports on animal with chronic colitis (Hayes et al., ; Moon et al., ). Therefore, low expression of IL‐10 mRNA in F935 group indicated reduction of inflammation in F935 mice of colitis.…”
Section: Discussionsupporting
confidence: 93%
“…L. reuteri F‐9‐35 exhibited excellent anti‐inflammatory activity in mice during the recovery period of colitis, but had no obvious effect during the induction period of colitis according to the clinical evaluation. Several studies also indicated that preventive intervention and the oral supplement with Lactobacillus during recovery period were more effective than acute colitis period in animal models (Hayes et al., ; Zheng et al., ). These findings indicated that Lactobacillus supplementation may accelerates UC recovery of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of probiotics increasingly is being used as a means to modify the composition of the gut microbiota beneficially in both health (6) and disease (3,14). Different probiotic formulations have proven effective in limiting disease in mouse models of IBD, including DSS (16,28). Given the association of the microbiota with DSS-induced behavioral changes, the effect of probiotics was assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Although multi-strain probiotic formulations need careful consideration in the development of therapeutic approaches, given the diversity of mechanisms of interaction of probiotics with cells of the immune system, increasing evidence for roles of soluble, bioactive mediators produced by some strains warrants careful consideration (Table 2). For example, both probiotic formulation and host inflammatory state influence probiotic efficacy in an acute colitis model comparing live and heat inactivated Bifidobacterium breve NCC2950 and soluble mediators from conditioned media administered at different time points (Hayes et al 2014). While direct interactions of probiotics with IEC and other cell types of the immune system have been intensively studied, there is a growing body of literature suggesting that probiotics also secrete or release an array of bioactive molecules with immunomodulatory activity Ruiz et al 2014).…”
Section: Probiotic-derived Bioactive Componentsmentioning
confidence: 99%